Let Us Look at People Without Passing Judgment: Book Review: Independent Theater Hungary, Michael Collins, Franciska Farkas, Dijana Pavlović, Richard R. O'Neill, Mihaela Drăgan – “Roma Heroes: Five European Monodramas”, Publisher: Women for the Future Association/ Independent Theater Hungary, May 29, 2020. - BÖJTHE, Pál (Studia Universitatis Babeș-Bolyai Dramatica, 2022)
Although it has been argued that the Roma theatre has existed in Europe for over a century, this phenomenon is still an enigma today due to lack of data. According to other opinions, this tradition dates back to 1930 and is linked to the former USSR, where the Romen Theatre was founded, serving the political ideology of the time. Whatever the origin of this cultural activity, Roma plays were never collected, much less printed in a volume. Currently, the only international Roma theatre festival in the world is held in Hungary. The readers of the volume hereby reviewed, are fortunate to see the first collection of Roma plays ever published in the world. Roma Heroes: Five European Monodramas is an exceptional collection of dramas and a special cultural history volume. The drama collection was compiled with great care and a lot of work. In the collection we can read five different dramas written by five European authors.